Control of Escherichia coli O157:h7, generic Escherichia coli, and Salmonella spp. on beef trimmings prior to grinding using a controlled phase carbon dioxide ([subscriptCP]CO[subscript2]) system - Tanus Meurehg, Carlos Arturo (Kansas State University, 2006)
This dissertation was designed to evaluate antimicrobial, quality, and shelf life effects of controlled phase carbon dioxide (CPCO2) on beef trimmings destined for ground beef. Critical parameters included pressure, temperature, exposure times, modified atmosphere conditions, and days of simulated retail display. 1500 psi CPCO2 for 15 min achieved 0.83, 0.96, 1.00, and 1.06 log reductions for Total Plate Count (TPC), Generic E. coli (GEC), E. coli O157:H7 (O157), and Salmonella spp. (SS), respectively. Bacterial reductions in ground beef and beef trimmings were similar (P≥0.05). CIE L*, a*, and b* values in raw patties showed no differences (P≥0.05) immediately after CPCO2 application on beef trimmings. Nevertheless, significant (P<0.05) interactions were found in pressure by packaging for L*, in pressure by packaging by days of simulated retail display for a*, and in packaging by days of simulated retail display for b* scores. Nevertheless, after 5 days of simulated retail display, L*, a*, and reflectance (630/580nm) ratios were similar for all treatments (P≥0.05), and b* scores were most acceptable with 1500 CPCO2 (P≥0.05), regardless of the packaging conditions. After 5 days of display, cooked patties showed similar (P≥0.05) values for crude protein (%CP) and crude fat (%CF), the extent of lipid oxidation (TBARS), was higher (P0.05) in aerobic trays than flushed packages with 100% CO2. Ground beef patties manufactured from beef trimmings treated with CPCO2scored higher values for tenderness (P0.05) than other treatments. In addition, no differences (P0.05) for juiciness, beef flavor intensity, or off flavor intensity were found between non-treated and the 1500 psi CPCO2 treated patties. Microbial control of spoilage organisms and foodborne pathogens in ground beef patties with CPCO2 application in beef trimmings was effective (0.6 to 1.2 logs). Lethality levels are comparable to other intervention strategies. Discoloration of beef trimmings after CPCO2 application may not be a concern for grinding purposes. Further packaging with 100% CO2 is viable for controlling spoilage and pathogenic microorganisms after packaging and during refrigerated storage, although discoloration of raw ground beef patties packaged with 100% CO2 may be a concern for product marketing.
Keywords: Carbon dioxide; Pathogen control; Ground Beef; Antimicrobial; Beef Trimmings; Agriculture, Food Science and Technology (0359); Biology, Microbiology (0410); Health Sciences, Public Health (0573)